Improving Brand Management in Commercial Enterprises (Eurasian Research Bulletin, 2022)
The article is devoted to determining the place and role of branding in the company management system. The author defines the concept and essence of branding, reveals the impact of branding on the company's performance, determines the role of the brandin business and consumer markets, and also analyses the problems and prospects of company brand management.